Alternative Media to Increase Knowledge About COVID-19 Vaccination in Children - Latif, Antinah; Besse Irna Tawaddud; Pratiwi Kusumowardhani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Several vaccination programs for children have not been maximized. The phenomenon of low vaccination coverage in children can be attributed, in part, to the role played by information distribution. Public service advertisements have been widely studied for their effectiveness but are limited to social media. Public service advertisements can be combined with a game. Games are used for health promotion media with various themes and are considered effective. Print media such as posters and combinations with games are media that need to be studied in this digital era. Aims: This study aims to develop public service advertising media to invite COVID-19 vaccinations. Method: This research uses research and development (R&D) with ADDIE stages. The intervention study was conducted in Makassar, South Sulawesi, and involved 40 grade 4 and 6 elementary school students and 65 parents. The intervention was carried out at school by combining posters and pinball games. Measurements are managed with a validated questionnaire to assess knowledge and perceptions. Data were analyzed using the Wilcoxon test. Results: 1) The quality of the media combination of posters and pinball games obtained a score of 3.023 which was included in the qualification of "good” with the recommendation "need some revision” 2) the application of a combination of posters and pinball games affected the knowledge of children; parents' knowledge is fair and good, and parents' perceptions are positive. Conclusion: In conclusion, the poster combination game is an alternative media to promote the uptake of COVID-19 vaccination among elementary school students and their parents.